How does digital finance influence green technology innovation in China? Evidence from the financing constraints perspective - Lin, Boqiang; Ma, Ruiyang (Journal of environmental management, 2022)
Green innovation activities of enterprises often fall into the dilemma of financing constraints. Hence, it is urgent that the financial system develops and becomes innovative, especially for a developing country like China. Existing literature mainly explores the influencing factors of green innovation from the environmental regulation, economic growth and government subsidies perspective. However, few papers critically study how digital finance influences green innovations. To explore the internal influencing mechanism of digital finance on the quantity and quality of green technology innovation, panel data of 271 prefecture-level cities from 2011 to 2019 in China is used. Based on theoretical analysis and empirical research, we get the following conclusions. First, digital finance can improve the quantity and quality of green technological innovation, which has become a significant driving force for green innovations in China. The results are still robust after the endogeneity tests. Second, the results of heterogeneous analysis indicate that the different dimensions of digital finance can improve green innovations. They include breadth of coverage, depth of use, and degree of digitization. The positive effect of digital finance is most substantial in eastern cities, followed by central cities, and weakest in western cities. Third, digital finance indirectly improves green innovation mainly by alleviating financing constraints. Our empirical results provide policy enlightenment for realizing the coordination of China's urban digital transformation and green economic development. •The effect of digital finance on the quantity and quality of green innovation is explored based on the actual background in China.•Digital finance has become a significant driving force for green innovation in China.•The different dimensions of digital finance can improve green innovations.•Digital finance plays a positive role in green technology innovation mainly by alleviating financing constraints.